Penerapan Konsep State Pattern Pada Game Engine (Studi Kasus Game Wipe It Off) - Firadi Surya Pramana; Eriq Muhammad Adams Jonemaro; Muhammad Aminul Akbar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Game that uses state machine as their agent behaviour decision making is common nowaday. However, there still lots of game engine that can't handle that requirement. State pattern is one of design pattern that could handle that requirement. Components of state pattern on game engine are defined and given the name of Initial State, Check State, and Handle State. Components of finite state machine on game are defined and given the name of Idle State, Moving State, and Cleaning State. State pattern on game engine implemented as a interface class that become thhe parernt of each state on finite state machine. Finite state machine on game implemented as an individual class that inherit the interface class from state pattern. State pattern tested with white-box testing and all the compoent are given the value of valid. Finite state machine tested with black-box testing and all the transitions are succeded and given the value of valid. With this game engine, therefore there is no game developer that will experience difficulty in developing game that uses state machine as their basic need.